Connections between 10-12 form Secondary School Students’ Tolerance and Their Relation to Their Activity - Sprindžiūnas, Andrius (Acta Paedagogica Vilnensia, 2002)
The research of more than 400 older students revealed some correlations among peculiarities of students’ classroom and after-classroom activities and some traits of their tolerance towards mates, parents and teachers. Being involved in meaningful activities, reflecting upon its purposes, initiative and creative participation, achieving good results were found as significantly related with various parameters of students’ tolerance in cognitive, emotional and practical aspects. Statistical analysis (Spearman correlation) revealed statistically significant relations among 10-12 form students’ frequent reflection about meaningfulness of their studies or after-school activities and deeper understanding the meaning of tolerance. Also those students who more often act on their own initiative or experiencing socially meaningful emotions were found more tolerant in the field of behaviour with their peers, parents and teachers. The represented data suggest in-direct ways how to promote tolerance by improving meaningful, voluntary, initiative and successful work in the school. Thus, participating in extra-curriculum activities could be held an important factor in fostering tolerance of the older secondary school students.